2007
DOI: 10.1093/europace/eum039
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation and myocardial necrosis in patients undergoing radiofrequency and cryoablation of isthmus-dependent atrial flutter

Abstract: Successful ablation of atrial flutter with cryoenergy is associated with less myocardial necrosis and platelet activation compared with ablation with RF energy. Increased platelet activation following RF ablation can be attenuated by concomitant treatment with aspirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…[12][13][14] As a result, it can be postulated that cryothermal ablation should result in a lower rate of ERAF because of the relatively reduced inflammatory reaction. 15,16 Interestingly, this was not observed in this prospective, randomized, multicenter study. Herein, we report a 52% incidence of ERAF <3 months of an index cryoballoon ablation procedure, which is consistent with nonrandomized observational studies after radiofrequency catheter ablation (16%-65%) as well as previous studies of cryoballoon ablation (44%).…”
Section: Incidence Of Early and Late Recurrencementioning
confidence: 58%
“…[12][13][14] As a result, it can be postulated that cryothermal ablation should result in a lower rate of ERAF because of the relatively reduced inflammatory reaction. 15,16 Interestingly, this was not observed in this prospective, randomized, multicenter study. Herein, we report a 52% incidence of ERAF <3 months of an index cryoballoon ablation procedure, which is consistent with nonrandomized observational studies after radiofrequency catheter ablation (16%-65%) as well as previous studies of cryoballoon ablation (44%).…”
Section: Incidence Of Early and Late Recurrencementioning
confidence: 58%
“…There is little data about evaluation of platelet activation during the EPS and RFA [23,25,27,28]. In the past, we studied the changes of platelets and endothelial functions during EPS, and we described the changes of platelet aggregation, release of thromboxane B2, and beta-thromboglobulin [29].…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, cryothermal ablation lesions are associated with minimal endothelial surface disruption and a lesser degree of platelet and the coagulation cascade activation when compared with RFCA. 2,20,21 Preclinical studies have demonstrated a significantly lower incidence of overlying thrombus (30.1% versus 75.8% despite the use of aspirin and heparin), and a lesser thrombus volume with cryothermal ablation compared with RF. 2,21 Moreover, in contrast to RF lesions where the extent of hyperthermic tissue injury was positively correlated with thrombus bulk, cryoablation lesion dimensions were not predictive of overlying thrombus volume.…”
Section: Lesion Characteristics Endothelial Integrity and Associatementioning
confidence: 99%